Optimization of Tax Collection Supervision in Increasing Local Original Revenue (PAD) by Gorontalo City Finance Agency - Arlin Nandita Yasin; Rukiah Nggilu; Jusrin Kadir (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the Optimization of Tax Collection Supervision in Increasing Regional Original Revenue (PAD) by the Gorontalo City Finance Agency. This research method uses descriptive qualitative research. The data collection techniques used are observation, interview, and documentation techniques. In accordance with the type of research used is qualitative analysis techniques. research results in the form of interviews conducted with research informants about Optimizing Supervision of Restaurant Tax Collection in Increasing Regional Original Revenue (PAD) by the Gorontalo City Finance Agency. The sub-focus used are: implementation standards, level of supervision, responsibility. From the statements or results of research with several informants above and from the observations of researchers, it shows that the standard implementation of restaurant tax collection by the Finance Agency has not been implemented optimally. Based on several statements or results of interviews with informants and from observations of researchers, it shows that the level of supervision carried out by the finance agency is still not optimal. From the results of interviews with several informants above, and from the observations of researchers, it shows that the responsibility of taxpayers is still a little less and has not reached a perfect number and the responsibility of the Finance Agency is also still not optimally carried out, this happens because there are still many taxpayers who do not understand the tools or sites they use in making transactions. This is one of the reasons why restaurant tax collection has not been optimized in increasing local revenue (PAD) in Gorontalo City.